Opioid versus opioid-free analgesia after surgical discharge: a systematic review and meta-analysis of randomised trials. Issue 10343 (18th June 2022) - Fiore, Julio F; El-Kefraoui, Charbel; Chay, Marc-Aurele; Nguyen-Powanda, Philip; Do, Uyen; Olleik, Ghadeer; Rajabiyazdi, Fateme; Kouyoumdjian, Araz; Derksen, Alexa; Landry, Tara; Amar-Zifkin, Alexandre; Bergeron, Amy; et al.
Summary: Background: Excessive opioid prescribing after surgery has contributed to the current opioid crisis; however, the value of prescribing opioids at surgical discharge remains uncertain. We aimed to estimate the extent to which opioid prescribing after discharge affects self-reported pain intensity and adverse events in comparison with an opioid-free analgesic regimen. Methods: In this systematic review and meta-analysis, we searched MEDLINE, Embase, the Cochrane Library, Scopus, AMED, Biosis, and CINAHL from Jan 1, 1990, until July 8, 2021. We included multidose randomised controlled trials comparing opioid versus opioid-free analgesia in patients aged 15 years or older, discharged after undergoing a surgical procedure according to the Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity definition (minor, moderate, major, and major complex). We screened articles, extracted data, and assessed risk of bias (Cochrane's risk-of-bias tool for randomised trials) in duplicate. The primary outcomes of interest were self-reported pain intensity on day 1 after discharge (standardised to 0–10 cm visual analogue scale) and vomiting up to 30 days. Pain intensity at further timepoints, pain interference, other adverse events, risk of dissatisfaction, and health-care reutilisation were also assessed. We did random-effects meta-analyses and appraised evidence certainty using the Grading of Recommendations, Assessment, Development, and Evaluations scoring system. The review was registered with PROSPERO (ID CRD42020153050). Findings: 47 trials (n=6607 patients) were included. 30 (64%) trials involved elective minor procedures (63% dental procedures) and 17 (36%) trials involved procedures of moderate extent (47% orthopaedic and 29% general surgery procedures). Compared with opioid-free analgesia, opioid prescribing did not reduce pain on the first day after discharge (weighted mean difference 0·01cm, 95% CI –0·26 to 0·27; moderate certainty) or at other postoperative timepoints (moderate-to-very-low certainty). Opioid prescribing was associated with increased risk of vomiting (relative risk 4·50, 95% CI 1·93 to 10·51; high certainty) and other adverse events, including nausea, constipation, dizziness, and drowsiness (high-to-moderate certainty). Opioids did not affect other outcomes. Interpretation: Findings from this meta-analysis support that opioid prescribing at surgical discharge does not reduce pain intensity but does increase adverse events. Evidence relied on trials focused on elective surgeries of minor and moderate extent, suggesting that clinicians can consider prescribing opioid-free analgesia in these surgical settings. Data were largely derived from low-quality trials, and none involved patients having major or major-complex procedures. Given these limitations, there is a great need to advance the quality and scope of research in this field. Funding: The Canadian Institutes of Health Research.